Overcoming resistance in advanced urothelial carcinoma: mechanisms of escape from antibody-drug conjugates and FGFR3 inhibition - Wummer, Brandon; Schwartz, Michael; Ciuro, Jordan; Ahmed, Shahid; Joshi, Shreyas S.; Narayan, Vikram M.; Carthon, Bradley C.; Bilen, Mehmet Asim; Brown, Jacqueline T. (Frontiers in Oncology, 2025)
For decades, platinum chemotherapy was the mainstay of treating metastatic urothelial carcinoma (mUC). More recently, checkpoint inhibitors (CPI) were an important addition to the armamentarium capable of inducing durable responses for a minority of patients. Management of mUC has changed significantly with the advent of antibody-drug conjugate (ADC) therapies and fibroblast growth factor receptor inhibitors (FGFRi). Enfortumab vedotin, a Nectin-4 targeting ADC, is now the first line therapy of choice in combination with pembrolizumab. Erdafitinib, a pan FGFR1–4 inhibitor, is approved for patients with susceptible FGFR3 alterations. There are multiple other agents in development within both therapeutic classes that hold promise. But most patients will still succumb to their disease, either via primary or secondary resistance. This review looks critically at the approved and pipeline ADC and FGFR-targeting agents of interest in mUC as well as known mechanisms of resistance by which their efficacy is dampened. We propose strategies for overcoming resistance including combination strategies, tumor microenvironment modification, and drug structure modification to maximize efficacy. The progress to date in mUC has been remarkable, but there is still significant work to do in this deadly disease and this review highlights the gap between current available therapeutics and cure that so desperately needs to be closed.